Peripheral T lymphocyte cytokine profile (IFNgamma, IL-2, IL-4) and CD30 expression/release during measles infection - F Vinante; M Krampera; L Morosato; A Rigo; S Romagnani; G Pizzolo (Haematologica, 1999)
BACKGROUND AND OBJECTIVE: Measles virus infection (MVI) has been reported to be characterized by an imbalanced Th(1/2)-type cytokine profile. CD30 has been proposed as a receptor preferentially associated with the Th(0/2)-type cytokine pattern. The aim of this study was therefore to define the peripheral T lymphocyte cytokine profile and to test which CD30 expression pattern it was associated with in MVI. DESIGN AND METHODS: The design of the study was a prospective evaluation with comparative analysis. The serum levels of the soluble form of CD30 (sCD30) were determined at diagnosis and at weekly intervals up to 4 weeks, using an ELISA, in 23 males (median age 19), who developed MVI while serving in the Italian army and who were admitted to the Infectious Disease Unit of the Military Hospital in Padua. In 10 of the patients at diagnosis we studied the lymphoid immunophenotype and, after non-specific ex vivo stimulation, the expression of IFNgamma, IL-2 and IL-4 by peripheral T cells using flow cytometry single cell analysis. In 3 patients such evaluations were also performed 7 weeks later. RESULTS: At diagnosis, we found (i) reduction of IFNgamma+/CD4+ T cells (p=0.048 vs controls) in the absence of substantial variation of IL-2+ and IL-4+ T cells (p=ns vs controls); (ii) expansion of CD30+/ CD4+ and CD30+/CD8+ T cell subsets (p<0.01 vs controls); (iii) high sCD30 values (median 61 U/mL; p<0.001 vs controls); (iiii) a context of lymphopenia (0. 728+/-0.292 lymph x10(9)/L). sCD30 remained elevated up to 4 weeks from MVI onset [median values 53, 49, 50, 34 U/mL after 1, 2, 3 and 4 weeks, respectively (p=ns between different time points)]. In 3 patients tested 7 weeks after diagnosis, we still observed decreased IFNgamma production by CD4+ and CD8+ T cells (p=0.05 and <0.01, respectively vs controls) and reduction of CD4+ and CD8+/IL-2+ T cells (p<0.01). INTERPRETATION AND CONCLUSIONS: MVI was characterized by featuresof inadequate Th/Tc(1) activation associated with increased circulating CD30+ T cells and elevated sCD30 levels, supporting a correlation between Th/Tc status and CD30 expression/release pattern in vivo.